Simulation of a mechanical vibratory system under rotating unbalance excitation and damped by shape memory alloy - Silva, Michel (2019)
This work presents a numerical simulation of mechanical vibratory systems (MVSs) under rotating unbalance and damped by a shape memory alloy (SMA) element. Due to pseudoelastic hysteretic behaviour, SMAs can dissipate energy and provide damping capabilities to the structure, which leads to a passive structural vibration control. The algorithm utilizes was implemented in Matlab, based in Helmholtz free energy deduction that results in a cosine constitutive model. The results made clear the dissipative capability of SMAs due to their hysteretic behavior.